2017
DOI: 10.1001/jamaophthalmol.2017.0261
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Vascular Microcirculation in Eyes With Glaucoma and Single-Hemifield Visual Field Loss

Abstract: IMPORTANCE Understanding the differences in vascular microcirculation of the peripapillary retinal nerve fiber layer (RNFL) between the hemispheres in eyes with glaucoma with single-hemifield visual field (VF) defects may provide insight into the pathophysiology of glaucoma.OBJECTIVE To investigate the changes in the microcirculation of the peripapillary RNFL of eyes with glaucoma by using optical microangiography. DESIGN, SETTING, AND PARTICIPANTSEyes with glaucoma and single-hemifield VF defect and normal ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 40 publications
8
70
0
Order By: Relevance
“…Three studies investigated glaucoma eyes with visual field defects in a single hemifield [30, 76, 79]. Interestingly, their findings regarding the perimetrically intact hemiretina could give information about the pathophysiology of glaucoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated glaucoma eyes with visual field defects in a single hemifield [30, 76, 79]. Interestingly, their findings regarding the perimetrically intact hemiretina could give information about the pathophysiology of glaucoma.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, their findings regarding the perimetrically intact hemiretina could give information about the pathophysiology of glaucoma. The first study found significantly lower OCTA parameters (vessel density and blood flow index) with normal RNFL in the perimetrically intact hemiretina [79]. The second study found a significantly lower RNFL with normal vessel density in the perimetrically intact hemiretina [30].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the other parameters, RNFL thickness and GCC thickness, which would be influenced by vascular flow [33], were worse in the progressed glaucoma groups of the current study at the last visit. Similar conditions were also found in VF defects, which may correlate with basal vascular impairment compared to HTG with good medical control.…”
Section: Discussionmentioning
confidence: 92%
“…The main structural parameters of glaucoma include RNFL thickness and GCC thickness, which are influenced by vascular flow [33]. The SmVD in the progressed HTG group is correlated with VF defects, RNFL, and GCC, while both the SmVD and the DmVD in the progressed NTG group were associated with the RNFL and GCC thickness alterations, and the FAZ in the progressed NTG group is correlated with a change in VF defects.…”
Section: Discussionmentioning
confidence: 99%
“…The flow index (mean decorrelation value on the en-face retinogram) and vessel density (area occupied by large vessels and microvasculature), have been shown to be associated with disease severity as reflected by SAP global indices (38). Additional studies demonstrated a reduction in peripapillary vessel density in the hemispheres corresponding to hemifield defects in visual fields (39) (40). In eyes with glaucoma and a single-hemifield defect, diminished vascular density of the macular and peripapillary regions was also demonstrated in unaffected hemifields (41).…”
Section: Novel Oct Technologies and Applicationsmentioning
confidence: 99%